The state of developmental states in Africa - Molokwane, T.; Mokaloba, M.; Motshegwa, B. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
The role of the state in promoting economic growth and social progress in the developing world has been a subject of deliberation globally among development experts and policy analysts. The state-led macro-economic planning seen largely in the late 20th Century, led to the emergence of new economies mainly in Asia with some in Africa experiencing economic success. Developmental state scholarly debates include attempts to explain why some developmental state theorists treat the state as a technocratic body separate from class relations which obscures the contradictory nature of state-led development. Scholars further argue that the conceptualisation of the developmental state is marked by methodological nationalism which leads to its proponents obscuring the global context of the developmental process, thereby reproducing a superficial external-internal contradiction. The research methods adopted are exploratory approach within an intrepretivist research paradigm. Data analysed is mainly secondary acquired through desktop research. The study explores contemporary factors different to those previously known to have facilitated socio-economic development in these states. The East Asian experience illustrates that governments in this sub-region transformed their economies from agrarian to the most advanced industrial economies. To the contrast, in Africa, save for a few exceptions, countries continually experience challenges in attaining high levels of socio-economic growth and development. The state of underdevelopment in the region is currently supported by authoritarian regimes with leaders who often attempt to temper with the constitutions to extend their stay in office. The advent of COVID-19 pandemic is also shaping the development landscape in Africa as countries continue to receive finding from multilateral agencies to assist their economies. Further to these, incidents of embezzlement of state funds have also been reported in countries that were previously not associated with such.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Africa; Asia; Development; Developmental state; Economy; Economic development -- Developing Countries; Sustainable development -- Developing Countries